Dissecting the role of salicylic acid in mediating stress response in mungbean cultivars concurrently exposed to Macrophomina phaseolina infection and drought stress - Kumari, Nilima (Plant physiology and biochemistry : PPB, 2024)
Copyright © 2024 Elsevier Masson SAS. All rights reserved.